The importance of knowing how to talk about illness without applying the concept of illness - Nordby, Halvor (Nursing philosophy, 2004)
The paper explores consequences of applying the view that illness is negative first-person experience in caring practice. The main reason this is an important issue is that it is empirically documented that patients conceive of illness in different ways. Communicating about illness in caring practice can therefore involve difficulties. I argue that many of these difficulties can be avoided if nurses focus directly on the extension of the concept of illness - patients’ experiences like the state of being in pain - and not on how this extension is represented as (the intension) illness. This argument is compatible with different views on the nurse-patient relationship as a communicative process. All it requires is the acceptance of minimal assumptions about concepts and concept possession. The argument has a descriptive and a normative dimension. It is descriptive in the sense that it seeks to use concepts from philosophy of mind to explain how many nurses succeed in talking about illness without applying the concept of illness. It is normative in the sense that it provides a philosophical justification for this practice.